PELAKSANAAN PROGRAM KESETARAAN PAKET C DI PKBM PELITA RIAU KELURAHAN LIMBUNGAN BARU KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Nelhayati '; Wilson '; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The formulation of the problem in this research is how is the implementation of package equality program C in PKBM Pelita Riau Limbungan Baru Village, Rumbai Pesisir Kota Pekanbaru Sub District? The purpose of this research is to know the implementation of package equality program C in PKBM Pelita Riau Limbungan Baru Village, Rumbai Pesisir Kota Pekanbaru Sub District. The type of this research is descriptive with qualitative approach. The subject of this study as many as 3 people, the technique of data source retrieval is by snowball sampling. This research instrument uses participatory observation, semiterstruktur interview and documentation. The results of the analysis carried out can then draw the conclusions of the implementation of the package equality program C through three stages, namely planning, learning process and evaluation.Keywords : Implementation, Program,Aquality, Package C, PKBM